Genetic Evaluation of Growth and Survival-Related Traits in Yesso Scallop Patinopecten yessoensis in Sea-Based Culture System - Wu, Fucun; Liu, Chao; Zhang, Jibiao; Zhang, Guofan (Frontiers in Marine Science, 2022)
Worldwide, the bivalve aquaculture industry has realized or recognized the potential gains from selective breeding programs using phenotypic and pedigree data. Yesso scallop Patinopecten yessoensis are among the most important commercial shellfish in China. A family-based breeding program to investigate the genetic variations for growth and survival-related traits at suspended and bottom environments of sea-based culture systems was reported in this study. We proposed and conducted a novel phenotyping technique to longitudinally evaluate the shell heights in the yesso scallop. At harvest after rearing for 20 months, the individual shell heights at 6, 10, 16, and 20 months were simultaneously obtained by the growth rings in the outer shells of the animals. Meanwhile, the body weight (BW) of the survived individuals at harvest was also recorded. Variance components and genetic parameters for growth and survival-related traits were estimated using an animal and threshold model, respectively. In the suspended environment, the heritability estimates for BW and shell heights at specific ages ranged from moderate to high (0.328–0.853). The estimated correlations between shell heights at contiguous ages were consistently high, ranging from 0.890 to 0.958 but decreased with increasing intervals between ages (0.496–0.828). The estimated correlations between shell heights at contiguous ages and BW at harvest were similar, ranging from 0.535 to 0.983. The heritability estimates for individual survival at harvest were at a low level of 0.128 by the probit-threshold model. While at the bottom environment, estimates of heritability for growth and survival-related traits were similar but slightly lower than those at the suspended environment. Furthermore, the genetic correlation for BW between the two environments was very small, which probably indicates genotype-by-environment interaction effects for growth in the yesso scallop. The study can provide prior information, which might develop a new idea for selection in this species. The results are discussed concerning selection work with yesso scallop, and solutions for accurate estimation of genetic parameters and increasing genetic gain are also outlined.